E-cadherin loss alters cytoskeletal organization and adhesion in non-malignant breast cells but is insufficient to induce an epithelial-mesenchymal transition - Chen, Augustine (BioMed Central, 2014)
BACKGROUND: E-cadherin is an adherens junction protein that forms homophilic intercellular contacts in epithelial cells while also interacting with the intracellular cytoskeletal networks. It has roles including establishment and maintenance of cell polarity, differentiation, migration and signalling in cell proliferation pathways. Its downregulation is commonly observed in epithelial tumours and is a hallmark of the epithelial to mesenchymal transition (EMT). METHODS: To improve our understanding of how E-cadherin loss contributes to tumorigenicity, we investigated the impact of its elimination from the non-tumorigenic breast cell line MCF10A. We performed cell-based assays and whole genome RNAseq to characterize an isogenic MCF10A cell line that is devoid of CDH1 expression due to an engineered homozygous 4 bp deletion in CDH1 exon 11. RESULTS: The E-cadherin-deficient line, MCF10A CDH1-/- showed subtle morphological changes, weaker cell-substrate adhesion, delayed migration, but retained cell-cell contact, contact growth inhibition and anchorage-dependent growth. Within the cytoskeleton, the apical microtubule network in the CDH1-deficient cells lacked the radial pattern of organization present in the MCF10A cells and F-actin formed thicker, more numerous stress fibres in the basal part of the cell. Whole genome RNAseq identified compensatory changes in the genes involved in cell-cell adhesion while genes involved in cell-substrate adhesion, notably ITGA1, COL8A1, COL4A2 and COL12A1, were significantly downregulated. Key EMT markers including CDH2, FN1, VIM and VTN were not upregulated although increased expression of proteolytic matrix metalloprotease and kallikrein genes was observed. CONCLUSIONS: Overall, our results demonstrated that E-cadherin loss alone was insufficient to induce an EMT or enhance transforming potential in the non-tumorigenic MCF10A cells but was associated with broad transcriptional changes associated with tissue remodelling. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2407-14-552) contains supplementary material, which is available to authorized users.